Public development sustainability values: a case study in Sepang Malaysia - Zurina Mahadi,; Rabiatul Jannah Mohamad,; Hukil Sino, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The concept of sustainable development has been implemented in Malaysia for more than a decade. Nevertheless, the issues of unsustainability still persist, raising questions about whether or not the values held by local populations pertaining to development processes are compatible with sustainable development values. This study was conducted in Sepang, Selangor to explore the values of public in the development process by using qualitative approach. The data was gathered from in-depth interviews and focus group discussions with the participants recruited through purposive sampling. Fourty participants have participated in this study. The transcript was analysed using thematic analysis to identify the theme values and the values categories. This study has identified four themes and twelve categories of public values in development. The themes were freedom, security, environment and development. The sustainability characteristics of every theme and category were explored by comparing them to existing established sustainable development values. It was evident that every theme and category of values displays sustainability characteristics despite public limited knowledge about sustainable development concepts. These findings therefore concluded that in principle, the unsustainability issues in this area did not result from the incompatibility of public development values with those of sustainable development. The implication of these findings is that the value systems of local people are already in harmony with the concept of sustainable development and could be effectively integrated into the local sustainable development framework.